2021
DOI: 10.1002/jcp.30256
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin is sensitive to actomyosin tension in human periodontal ligament fibroblasts

Abstract: Periodontal ligament fibroblasts (PdLFs) are an elongated cell type in the periodontium with matrix and bone regulatory functions which become abnormal in periodontal disease (PD). Here we found that the normally elongated and oriented PdLF nucleus becomes rounded and loses orientation in a mouse model of PD. Using in vitro micropatterning of cultured primary PdLF cell shape, we show that PdLF elongation correlates with nuclear elongation and the presence of thicker, contractile F‐actin fibers. The rounded nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The activation of renal fibroblasts is also characterized by up-regulations of α-SMA and F-actin incorporated into the stress fibers 66 – 68 . During the transition of fibroblasts from quiescent state to their activated form, up-regulations of α-SMA and F-actin have been reported to promote myofibroblast contractile activity 67 , 69 . Several lines of evidence have indicated that α-SMA-associated contraction is involved in ECM organization 67 , 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…The activation of renal fibroblasts is also characterized by up-regulations of α-SMA and F-actin incorporated into the stress fibers 66 – 68 . During the transition of fibroblasts from quiescent state to their activated form, up-regulations of α-SMA and F-actin have been reported to promote myofibroblast contractile activity 67 , 69 . Several lines of evidence have indicated that α-SMA-associated contraction is involved in ECM organization 67 , 70 , 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the study concluded that OPG is responsive to actomyosin tension in human periodontal ligament fibroblasts. 55 a. Cytokines. PD is a chronic inflammatory disease initiated by microbial dysbiosis.…”
Section: Biomarkers Used For the Diagnosis Of Pdmentioning
confidence: 99%
“…Periodontal disease also leads to round PDLF nuclear morphology in vivo, which is accompanied by a reduction in actomyosin contractility and a decrease in OPG synthesis from PDLFs. This additional mechanism might, therefore, contribute to this shift in biochemical signaling and is a direct consequence of disturbed MT (Figure 4) [265].…”
Section: Porphyromonas Gingivalis-derived Proteases: a "Heavy Load" For The Periodontiummentioning
confidence: 99%